Fission product release from high and low-enriched uranium fuels of the ivg.1m research reactor - Medetbekov, B.S.; Vurim, A.D.; Prozorova, I.V.; Popov, Yu.A. (Karaganda University named after academician E.A.Buketov, 2023)
The research involved conducting resource tests on two experimental water-cooled technological channels (WCTCs) utilizing low-enriched uranium (LEU) fuel within the IVG1.M research reactor. This testing was a crucial step in the reactor's conversion from highly enriched uranium (HEU) fuel to LEU. The research focused on two key parameters, namely the specific activity and the relative release of fission products (FPs) into the coolant, to evaluate the tightness of the fuel element cladding. A gamma-spectrometric sampling method was proposed to determine the relative release of FPs, which involved assessing the specific activity of the coolant, calculating the release rate (Release), the born rate (Born), and the R/B ratio of FPs. Comparative gammaspectrometric measurements were conducted to analyze the content of FPs and activation products (AP) in the coolant of WCTCs utilizing both LEU and HEU during the tests. From the comprehensive list of detected radionuclides in the IVG.1M reactor coolant, well-identified reference radionuclides recommended for monitoring fuel element cladding tightness were carefully selected. The results of the study provided insights into the specific activity and relative release of FPs, demonstrating that quantitative values for the relative release of FPs from WCTCs using LEU and HEU fuel were comparable.
Keywords: coolant; fuel element; fuel element cladding; fission products; relative release of fission products; gamma-spectrometry